Infinitely many solutions for sublinear indefinite nonlocal elliptic equations perturbed from symmetry. (March 2017) - Zhang, Liang; Chen, Yi
Abstract: This paper is concerned the existence of infinitely many solutions for perturbed sublinear indefinite elliptic equations involving the nonlocal operator. By using a variant of Rabinowitz's perturbation method, we study the effect of high order non-odd perturbations which break the symmetry of the associated energy functional and show how a sequence of small negative energy solutions persists under broken symmetry situations.